(untitled) - Schengrund, Cara-Lynne; Yu, Robert K. (Advances in Neurobiology,, 2014)
A thorough introduction is provided to the variety and complexity of the roles that glycoconjugates play in the cells of the nervous system. Basic information as well as the latest developments in neural glycobiology are discussed. Topics covered range from the structure and metabolism of the saccharide chains and current approaches used in their study, to changes glycoconjugates undergo during development and aging of the nervous system and the roles they have in neurological disease. The breadth and depth of topics covered make it an essential reference for those new to the field as well more seasoned investigators.